Penerapan Internet of Things pada Greenhouse - Zulfikar Mubarak Maren Saputra; Irving Vitra Paputungan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Climate change has many causes, one of which is an increase in atmospheric temperature or commonly called global warming. As a result of global warming, the climate around plants can become unfavorable to support the growth of crop production. One of the agricultural sectors affected by global warming is the greenhouse. These problems can be solved by implementing the internet of things and the nRF24L01 communication module in the greenhouse. This system will provide information in the form of temperature sensor readings, soil moisture sensors, soil pH and light intensity that can be seen without having to come to the greenhouse because this tool will send the monitoring results using the nRF24L01 communication module. Greenhouse owners or farmers can monitor the condition of their plants through the android-based blynk application, so they can maximize their harvests. An analysis was carried out regarding plants that use the internet of things and those that do not use the internet of things for several days. The results obtained from this analysis are plants that use the internet of things have better results and are cheaper in terms of costs.